Onabotulinumtoxina in the Prevention of Migraine in Pediatric Population: A Systematic Review - Artemis Mavridi; Aine Redmond; Paraschos Archontakis-Barakakis; Petya Bogdanova-Mihaylova; Christina I. Deligianni; Dimos D. Mitsikostas; Theodoros Mavridis (Toxins, 2024)
Migraine is a leading cause of disability worldwide, yet it remains underrecognized and undertreated, especially in the pediatric and adolescent population. Chronic migraine occurs approximately in 1% of children and adolescents requiring preventive treatment. Topiramate is the only FDA-approved preventative treatment for children older than 12 years of age, but there is conflicting evidence regarding its efficacy. OnabotulinumtoxinA is a known and approved treatment for the management of chronic migraine in people older than 18 years. Several studies examine its role in the pediatric population with positive results; however, the clear-cut benefit is still unclear. OnabotulinumtoxinA seems not only to improve disability scores (PedMIDAS) but also to improve the quality, characteristics, and frequency of migraines in the said population. This systematic review aims to summarize the evidence on the efficacy, dosing, administration, long-term outcomes, and safety of onabotulinumtoxinA in pediatric and adolescent migraine. Eighteen studies met the eligibility criteria and were included in this review. The mean monthly migraine days (MMDs), decreased from of 21.2 days per month to 10.7 after treatment. The reported treatment-related adverse effects were mild and primarily injection site related and ranged from 0% to 47.0%. Thus, this review provides compelling evidence suggesting that OnabotulinumtoxinA may represent a safe and effective preventive treatment option for pediatric migraine.